KONTRIBUSI TERNAK SAPI SEBAGAI ALAT TRANSPORTASI OLEH PETANI KEBUN KELAPA DI KECAMATAN JAILOLO KABUPATEN HALMAHERA BARAT - Panawa, Albert; Lainawa, J; Lenzun, G D; Elly, F H (ZOOTEC, 2014)
ABSTRACT CONTRIBUTION OF CATTLE AS THE TRANSPORTATION INSTRUMENT OF FARMERS ON COCONUT PLANTATION AT JAILOLO DISTRICT, WEST HALMAHERA REGENCY. Total of cattle at Jailolo district in year of 2013 were 3,410 heads and bred traditionally by household farmers. Cattle at Jailolo district were used by household farmer as transportation instrument around plantation areas. The problem was that cattle contribution on farmer income as transportation instrument had not been evaluated. The objective of this study was to evaluate cattle contribution on farmer income as transportation instrument in coconut plantation. Research was done using survey method. Data were found from household farmers and found from related offices. Samples of villages were taken using purposive sampling. Household farmers were defined using simple random sampling involving 30 samples. Results showed that cattle as transportation instrument contributed work time period of 1,284 hours per period of plantation including coconut, banana and nutmeg production. Transportation instrument involving cattle contributed household income of Rp. 23,095,000 or 8,21 percents of the total household income per production period of coconut plantation.Â  Key words: Transportation instrument, Cattle, Household farmers, Income contribution, Jailolo district, West Halmahera Regency.Â